ESG: Uma análise sobre as dimensões que compõem o índice de investimentos ISE-B3: Brasil, Bolsa, Balcão - Medeiros, Jefferson da Silva (2024)
This study aimed to analyze ESG (Environmental, Social, and Governance) factors in the composition of the ISE (Corporate Sustainability Index) listed by B3 (Brasil, Bolsa, Balcão) in Brazil. The research corpus evaluated the indicators comprising the ISE, including its five foundational dimensions: Human Capital, Corporate Governance and Senior Management, Business Model and Innovation, Social Capital, Environment, and the CDP-Climate Change dimension. The research sample consisted of companies selected for the 2022 (based on 2021 data), 2023 (based on 2022 data), and 2024 (based on 2023 data) ISE portfolios. To achieve the proposed objective, a quantitative analysis was conducted using descriptive and exploratory approaches, supported by a bibliographic review encompassing all publicly available research related to ESG, ISE, and corporate sustainability. Content and statistical analyses were performed on the ISE and its dimensions. From the analyses conducted, it was observed that of the 6 dimensions considered as variables, over the past 3 years, 5 dimensions showed an increase in scores, while one dimension showed a decrease. At the same time, it is important to highlight the growth in the number of companies beginning to be part of the ISE B3 index. Among the correlation matrices analyzed, the normality of the data for Pearson correlation stands out, showing a strong and significant relationship between the environmental and CDPClimate Change dimensions. To validate the studies conducted, the generated linear regression observed a significant relationship between the variables Human Capital x Corporate Governance and Senior Management, Human Capital x Business Model and Innovation, Corporate Governance and Senior Management x Business Model and Innovation, and Business Model and Innovation x Social Capital, demonstrating that these variables exhibit greater synergistic effects among themselves. Regarding the proposed study objective, the research highlights the importance of focusing on human capital, business model and innovation, and corporate governance and senior management, as these dimensions have the greatest impact on score ratings and the studied relationships. Understanding the relationships between Human Capital and other variables is essential for formulating effective management strategies to achieve organizational sustainability.